Non-pharmacological educational and self-management interventions for people with chronic headache: the CHESS research programme including a RCT - Underwood, M; Achana, F; Carnes, D; Eldridge, S; Ellard, DR; Griffiths, F; Haywood, K; Hee, SW; Higgins, H; Mistry, D; Mistry, H; Newton, S; et al. (NIHR Journals Library, 2023)
Background:Headaches are a leading cause of years lived with disability. For some people, headaches become chronic and disabling, with treatment options being primarily pharmaceutical. Non-pharmacological alternative treatment approaches are worthy of exploration.